Ribonucleases in Mendelian disease: Characterization and insight from model organisms - Annasha Dutta; Anastasiia Zaremba; Paulina Jackowiak (Genes and Diseases)
Ribonucleases (RNases), essential for RNA metabolism, are implicated in human diseases, including neurodevelopmental, developmental, hematopoietic and other dysfunctions through mutations that disrupt their enzymatic functions. Exploring RNase mutations across organisms offers insights into Mendelian diseases, facilitating molecular dissection of pathological pathways and therapeutic development. By employing model organisms, our analysis underscores the evolutionary conservation of RNase genes, facilitating deeper insights into disease mechanisms. These models are vital for uncovering rare molecular dysfunctions and potential therapeutic targets, demonstrating the effectiveness of integrated research approaches in addressing complex genetic disorders. Drawing from phylogenetic analyses, literature survey, and databases documenting the effects of human disease-causing mutations, the review highlights the significance and advantages of employing model organisms to study specific Mendelian disorders.